A clawback compensation scheme and its effect on method options for earnings management - Ratna Candra Sari; Mahfud Sholihin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
This study aims to examine the effectiveness of the adoption of clawback in reducing the intention of managers to manipulate earnings. This study differs from previous literatures which are mainly conducted in low uncertainty avoidance and high individualism cultures using an archaival method since it is conducted in a country with high uncertainty avoidance and low individualism culture using an experimental approach. This study is important because previous studies indicate that national culture provides important explanations or the variance of the effectiveness of compensation schemes. The respondents are students of postgraduate of accounting who have work experience in the field. The study was conducted between February-March 2018. The result of this study shows that the adoption of clawback reduces managers’ intention to engage in earnings manipulation, especially accrual manipulation. However, the study also finds that clawback motivates managers to engage in earnings management using a method that is more difficult to be detected by regulators and auditors.